Pengaruh Kompetensi dan Budaya Organisasi Terhadap Produktivitas Kerja Karyawan Melalui Motivasi Kerja Pada PT Union Teknika - Ayu Widiya Sari; Erni Yuningsih; Tini Kartini (Institut Nalanda, 2023)
Productivity is an important factor for companies to achieve the goals set. Research objectives to determine the effect of competence and organizational culture on employee productivity through work motivation as an intervening Variable. The sample used is all employees of PT Union Teknika totaling 64 employees. The results showed that both simultaneously and partially competence and organizational culture affect work motivation, simultaneously and partially competence, organizational culture and work motivation are directly positive and significant to employee work productivity, work motivation is able to mediate the effect of competence on employee work productivity and work motivation is not able to mediate the effect of organizational culture on employee work productivity.